Professional responsibility applied to drug surveillance: a study case in México - Novoa-Heckel, Germán; Asbún-Bojalil, Juan; Sevilla-González, María de la Luz (Acta Bioethica, 2016)
The international pharmacovigilance system collects adverse drug events reported by physicians in their clinical practice. Adverse drug reactions (ADR) reported are scarce. We designed a questionnaire based on a 5-point Likert scale. The questionnaire (24 questions) was administered to a sample of physicians in Mexico City. Questionnaire responses indicated that having pharmacovigilance systems is important. Despite this, nearly three quarters of respondents did not know how to report an adverse drug reaction, and two-fifths were not willing to do so. Three quarters believed that education regarding reporting and its methods should be initiated during medical school. The results from our questionnaire suggest that medical school training in ADR report writing should be implemented. Good protocols have to be in place to ensure that ADR report forms have easy-to-follow guidelines and are easy to complete. It is recommended that the programs of training and medical education generate conscience of responsability towards the report of ADRs.